The Influence of Work Dicipline and Work Stress on Employee Performance PT. Asia Toserba Tasikmalaya (Case Study on Employees of PT. Asia Toserba Tasikmalaya City in the Sales Assistant) - Andina Nopianti; Rita Tri Yusnita; Ai Kusmiati Asyiah (Journal of Indonesian Management, 2023)
This study aims to determine the effect of work discipline, work stress on employee performance at PT. Asia Toserba Tasikmalaya (Case Study on Employees of PT. Asia Toserba Tasikmalaya City in the Sales Clerk). The method used is a quantitative approach with a sample of 100 respondents from sales clerks at PT. Asia Department Store Tasikmalaya City. The data used are primary data and secondary data. The analytical tool used in this study is multiple linear regression analysis using SPSS version 25. The results of this study indicate that simultaneously work discipline and work stress have a significant effect on employee performance. Partially work discipline has a significant effect on employee performance. Partially, work stress has a significant effect on employee performance.